Molecular Hydrogen Production by Clostridium Pasteurianum During Utilization of Coffee Waste (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
The production of hydrogen (H₂) through biological methods, particularly dark fermentation, not only enables renewable energy generation but also facilitates efficient recycling of organic waste. The production of H₂ by the Clostridium pasteurianum DSM525 strain was investigated using varying concentrations of untreated coffee waste (20–60 g L⁻¹) as a carbon source. Experiments were conducted both in the presence and absence of glucose to evaluate the efficiency of coffee waste (Spent coffee grounds) alone as a carbon source. Clostridium pasteurianum is a strictly anaerobic, gram-positive, spore-forming, mesophilic bacterium that metabolizes various carbohydrates, particularly glucose, during dark fermentation to produce H₂. The results showed that in the absence of glucose, the maximum H₂ yield was ~6 mM at 96 hour of growth when 40 g L⁻¹ coffee waste was applied, maintaining a relatively stable level until the end of fermentation. A similar trend was observed with 60 g L⁻¹ coffee waste. In conditions with 60 g L⁻¹ coffee waste, slower but stable growth was noted, with the maximum H₂ production (~3 mM) observed at 72 hour of growth. Meanwhile glucose addition lead to significantly higher yields: the highest H₂ yield was recorded at 96 hour with 60 g L⁻¹ coffee waste constituting 55mM. For 20 g L⁻¹ and 40 g L⁻¹ coffee waste, the maximum H₂ production ~36 mM was observed at 72 hour. Thus, the presence of glucose significantly enhances the growth of Clostridium bacteria across all groups compared to conditions without glucose. These findings indicate that coffee waste without time-consuming treatment can serve as an effective carbon source for bio-H₂ using Clostridium pasteurianum bacterial strain and further process optimization may further lead to cost-effective productions.
Keywords: Bio-H₂; Clostridium pasteurianum; Spent coffee grounds